Estimating the energy contribution during single and repeated sprint swimming - Peyrebrune, M. C.; Toubekis, A. G.; Lakomy, H. K. A.; Nevill, M. E. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The extent to which aerobic processes contribute to energy supply during short duration sprint swimming is not known. Therefore, the energy contribution to a maximal 30 s fully tethered swim (FTS), and repeated 4 × 30 s high intensity semi-tethered swimming bouts (STS) with 30 s of passive rest at 95% of the 30 s FTS intensity was estimated in eight elite male swimmers. Blood lactate concentration and pH after the 4 × 30 s test were 12.1 ± 3.6 mmol/L and 7.2 ± 0.1, respectively. Accumulated oxygen demand was estimated to be 50.9 ± 9.6 mL/kg and 48.3 ± 8.4, 47.2 ± 8.5, 47.4 ± 8.3, and 45.6 ± 6.8 mL/kg for the 30 s FTS and 4 × 30 s bouts, respectively. Accumulated oxygen uptake was 16.6 ± 3.6 for the 30 s FTS and progressively increased during the 4 × 30 s bouts 12.2 ± 2.1, 21.6 ± 2.5, 22.8 ± 1.8, and 23.5 ± 2.0 mL/kg (P < 0.01). The estimated aerobic contribution therefore was 33 ± 8% for the 30 s FTS and 25 ± 4, 47 ± 9, 49 ± 8, 52 ± 9% for bouts 1-4 during the 4 × 30 s STS test (P < 0.01). The results underline the importance of aerobic energy contribution during single and repeated high intensity swimming, which should be considered when prescribing swimming training sets of this nature.